Neuron-specific enolase in patients with acute and chronic schizophrenia, diversity of approaches: marker of neuronal death, neurodegeneration or neurodevelopmental theory in schizophrenia? a single-center case-control study - Sierakowska, Alicja; Niewiadomska, Ewa; Łabuda, Sebastian; Bieniasiewicz, Anna; Roszak, Mateusz; Łabuz-Roszak, Beata (Frontiers in Psychiatry, 2025)
IntroductionSchizophrenia is a mental illness that affects a diverse group of patients, but the underlying causes of the symptoms can vary. There is currently a lot of research being done on the use of biomarkers in the diagnosis of schizophrenia, including neuron-specific enolase (NSE). The aim of this study was to evaluate and compare NSE concentrations in the serum of patients with schizophrenia and to determine possible relationships between NSE and the duration and severity of positive and negative symptoms of schizophrenia.Materials and methodsThe study included 59 patients with schizophrenia and 60 healthy controls. NSE serum concentrations were assessed in all subjects. The Scale for the Assessment of the Negative Symptoms (SANS) and the Scale for the Assessment of the Positive Symptoms (SAPS) were used to assess the symptoms of schizophrenia.ResultsThe mean serum concentration of NSE in patients with schizophrenia was statistically significantly lower than in healthy controls. A weak negative correlation between NSE levels and the SANS score and a weak positive correlation between NSE levels and the SAPS score were found, but the results were not statistically significant. No relationship was reported between age, sex, disease duration, dependence on others or laboratory findings and NSE levels.DiscussionThe study found lower NSE levels in patients with schizophrenia. A tendency towards correlation between severity of negative symptoms of schizophrenia and decreased levels of NSE were observed. In addition, a trend was noted between an increase in NSE level and the severity of positive symptoms. The results of the experiment should be confirmed in further studies.